Morphophonemic changes in the formation of Ilongo verbs - Sucaldito, Perla S. 1945- (1973)
An attempt to analyze the morphophonemic changes that occur in the formation of Ilongo verbs, this paper aimed to describe the various shapes of phonemes in morpheme sequences and to identify the environment in which these phonemes appear. The data consisted of a list of 300 words gathered from Visayan magazines and from conversations among native speakers of Ilongo. The study revealed the following morphophonemic changes in Ilongo verb formation: assimilation, consonant change, vowel change, loss of phoneme, stress shift, metathesis, and reduplication. It is hoped that the findings in this study can be a starting point for a workable program in the teaching of Ilongo.
Vita.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: Hiligaynon language -- Morphophonemics; Hiligaynon language -- Verb